2020
DOI: 10.1002/ejlt.201900325
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein Isolate Coated Liposomes as Novel Carrier Systems for Astaxanthin

Abstract: In this work, whey protein isolate (WPI)‐coated astaxanthin‐loaded liposomes are prepared by combining the fabrication of liposomes with the layer self‐assembly deposition technique. The physical properties of such composite carriers are evaluated by zeta potential, particle size, distribution, encapsulation efficiency, and morphology. WPI‐ coated astaxanthin‐loaded liposomes display homodisperse distribution and high encapsulation efficiency with a WPI coating layer surrounding the surface of conventional lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…The affinity between phospholipids and oil can be used to form a protective layer on the surface of oleogels. However, a single phospholipid layer as an external structure may have degradation, aggregation, fusion and leakage of core materials problems, which will adversely affect the oleogels [17] .…”
Section: Introductionmentioning
confidence: 99%
“…The affinity between phospholipids and oil can be used to form a protective layer on the surface of oleogels. However, a single phospholipid layer as an external structure may have degradation, aggregation, fusion and leakage of core materials problems, which will adversely affect the oleogels [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Although high stability would be desirable in any case, it is especially relevant in the case of ingredients that need to be stored for long periods before use or if they are to be applied to foods in which degradation boosting (low pH, thermal treatments, presence of oxygen) or strong interactions with matrix components are expected. Multilayer structures—for example, those based on liposomes or oil-in-water emulsions—have shown greater physical stability and astaxanthin protection, as compared with uncoated or monolayer structures [ 51 , 81 , 82 ].…”
Section: Insights Into the Selection Of Encapsulation Methods And Wmentioning
confidence: 99%
“…In this sense, the application of multilayer structures appears as a promising strategy to improve astaxanthin stability. Qiang et al [ 51 ] and Pan et al [ 81 ] developed chitosan, lactoferrin or whey protein isolate-coated liposomes which showed an improvement of physical stability during storage or thermal treatment, reducing leakage and/or the thermal or light-induced degradation of astaxanthin, as compared with uncoated liposomes. Similar results were obtained by Liu et al [ 82 ], who found that multilayer-coated emulsions improved the chemical stability of encapsulated astaxanthin, as well as the aggregation stability of the lipid droplets at elevated ionic strengths and temperatures.…”
Section: Encapsulation Technologies To Improve the Technological Fmentioning
confidence: 99%
“…Biocompatibility, sustained-release characteristic, target capacity and the potential to encapsulate hydrophilic and lipophilic components are specific advantages of liposomes [29]. However, liposomes also have certain disadvantages that they are extremely sensitive to the external environment, and unstable which are subjected to degradation, aggregation, fusion, and leakage of core materials.…”
Section: Liposomementioning
confidence: 99%